Development of accessible educational resources: knowledge and practices of E-learning professionals - Monteiro Lima, Kaynara Beatriz (2025)
This study investigated the knowledge and practices of 21 developers of digital educational resources (DERs) at the Open University of the Unified Health System of the Federal University of Maranhão for people with hearing loss/deafness. An online questionnaire was used to collect sociodemographic data and information on knowledge and application of accessibility criteria. Most of the professionals were aware of the general accessibility criteria for producing EDRs, but not the specific guidelines for these resources. They knew that the lack of a window for translation into Libras compromises comprehension and that, in videos, the translation box should be in the bottom right-hand corner of the screen. They also recognized that the absence of subtitles in videos hinders comprehension. The majority did not use automatic validators. The results show a broad knowledge of accessibility criteria, a commitment to accessibility and inclusion practices, and the need for ongoing training in the area.